Adaptive Organizational Communication of ASEAN from an Autopoietic Systems Perspective - Dian Christianti; Hermin Indah Wahyuni (Center for Southeast Asian Social Studies (CESASS), 2017)
This article focuses on ASEAN after the establishment of its community in a systems perspective. The problem elicited in this research is how the ASEAN Secretariat's adaptive communication is able to cope with challenges stemming from the establishment. To answer the question, a case study is applied, using data collection techniques including document analysis, interview, and observation. The findings reveal that ASEAN adaptive communication has allowed the association to grow rapidly to deal with difficulties. It is not, however, as ideal as a system proposed by Luhmann.